Advancing Digital Health Equity: A Policy Paper of the Infectious Diseases Society of America and the HIV Medicine Association. (9th October 2020) - Wood, Brian R; Young, Jeremy D; Abdel-Massih, Rima C; McCurdy, Lewis; Vento, Todd J; Dhanireddy, Shireesha; Moyer, Kay J; Siddiqui, Javeed; Scott, John D
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has revolutionized the practice of ambulatory medicine, triggering rapid dissemination of digital healthcare modalities, including synchronous video visits. However, social determinants of health, such as age, race, income, and others, predict readiness for telemedicine and individuals who are not able to connect virtually may become lost to care. This is particularly relevant to the practice of infectious diseases (ID) and human immunodeficiency virus (HIV) medicine, as we care for high proportions of individuals whose health outcomes are affected by such factors. Furthermore, delivering high-quality clinical care in ID and HIV practice necessitates discussion of sensitive topics, which is challenging over video without proper preparation. We describe the "digital divide, " emphasize the relevance to ID and HIV practice, underscore the need to study the issue and develop interventions to mitigate its impact, and provide suggestions for optimizing telemedicine in ID and HIV clinics. Abstract : Social determinants of health impact readiness for telemedicine and other virtual healthcare. Disparities in telemedicine access in infectious disease and human immunodeficiency virus clinics should be quantified and addressed in order to enhance digital health equity.